2006
DOI: 10.1136/adc.2005.077750
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal socioeconomic and emotional factors on infant weight gain and weight faltering (failure to thrive): data from a prospective birth cohort

Abstract: In this setting, social and maternal characteristics had little influence on infants' weight gain, apart from a strong, but transient effect of postnatal depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 37 publications
4
83
2
Order By: Relevance
“…These results are partly consistent with the findings of Grote et al who found that Z-scores for weight-for-length at inclusion of infants of mothers with high Edinburgh postnatal depression scale (EPDS) scores were lower than of those with normal scores [22]. Results of our study showed that potential effects of depressive symptoms might be prolonged through 12 months of child life, this result is inconsistent with results of Wright et al study who suggested these effects might be transitional and not remains no longer at the first year of child's life [23].…”
Section: Discussioncontrasting
confidence: 99%
“…These results are partly consistent with the findings of Grote et al who found that Z-scores for weight-for-length at inclusion of infants of mothers with high Edinburgh postnatal depression scale (EPDS) scores were lower than of those with normal scores [22]. Results of our study showed that potential effects of depressive symptoms might be prolonged through 12 months of child life, this result is inconsistent with results of Wright et al study who suggested these effects might be transitional and not remains no longer at the first year of child's life [23].…”
Section: Discussioncontrasting
confidence: 99%
“…Although only 5% of children, by definition, will drop below this threshold at any one measurement point, about 10% will make a fall of this size at some time in the first year, but only about 5% will show a fall of this size sustained over a number of measurements (15) . The slowest gaining 5% roughly equates to a fall through two centile spaces (1 .…”
Section: Failure To Thrive/weight Falteringmentioning
confidence: 99%
“…We have now gathered a substantial body of evidence about the significance of weight faltering identified in this way, with most research done on children in the slowest gaining 5% of various representative populations compared with their birth centile (14)(15)(16) . Although only 5% of children, by definition, will drop below this threshold at any one measurement point, about 10% will make a fall of this size at some time in the first year, but only about 5% will show a fall of this size sustained over a number of measurements (15) .…”
Section: Failure To Thrive/weight Falteringmentioning
confidence: 99%
“…7 % and 18 . 8 % of 8-month-old and 12-month-old infants respectively have severe aversive feeding behaviour (67) . Research indicates that infants with reflux-type symptoms or colic, which are often related to non-IgE-mediated allergy to cow's milk and soyabean, are associated with major feeding problems that range from food refusal, gagging on introduction of lumpier textures and extreme anxiety during meal times (68,69) .…”
Section: Nutrient Content Of Major Food Allergens and How To Ensure Amentioning
confidence: 99%